2017
DOI: 10.1002/bdr2.1065
|View full text |Cite
|
Sign up to set email alerts
|

Congenital unilateral renal agenesis: Prevalence, prenatal diagnosis, associated anomalies. Data from two birth‐defect registries

Abstract: Our study provides estimates of prevalence of URA at birth. A longitudinal cohort from the antenatal period to puberty should be performed to determine the prognosis of the contralateral kidney among these children with isolated, associated with contralateral CAKUT and URA with extra-renal anomalies. Birth Defects Research 109:1204-1211, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…In the Netherlands, this was mainly attributable to a large proportion of anomalies of the collecting system (70.4%) and high coverage of prenatal screening. The average term at prenatal diagnosis in our study was similar to the study in France (26.6 ± 9.2 weeks) [5].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the Netherlands, this was mainly attributable to a large proportion of anomalies of the collecting system (70.4%) and high coverage of prenatal screening. The average term at prenatal diagnosis in our study was similar to the study in France (26.6 ± 9.2 weeks) [5].…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that CAKUTs are one of the most common defects associated with congenital heart defects [33, 34]. According to published studies, the most frequently reported nonurinary anomalies involve the genitourinary tract; central nervous system, musculoskeletal, digestive and cardiovascular systems, and chromosomal anomalies [2, 5, 11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As early as 1870, a Swiss surgeon, Reverdin, described unilateral renal absence (URA) in a man with CUAVD and an ipsilateral absence of SV (Reverdin 1870). Since then, numerous studies (Schlegel et al 1996;Casals et al 2000;Weiske et al 2000;Patat et al 2016;Mieusset et al 2017Mieusset et al , 2020 have confirmed that URA is found with CAVDs at a high rate of 5-40%, while the prevalence of URA at birth is nearly 1,000 times lower (4/10,000) (Laurichesse Delmas et al 2017). It is important to note that URA is found twoto-three times more frequently in patients with CUAVD (20-40% of the cases, with URA being predominantly ipsilateral) than in those with CBAVD (5-10% of cases).…”
Section: Definition Of the Cavd (Different Forms) History And Clinimentioning
confidence: 97%